Non-immune hydrops fetalis: A retrospective analysis of 151 autopsies performed at a single center - Kaykı, Gözdem; Örgül, Gökçen; Utine, Gülen Eda; Boduroğlu, Osman Koray; Yiğit, Şule; Yurdakök, Murat; Talim, Beril; Orhan, Diclehan; Akçören, Zuhal; Güçer, Şafak; Beksaç, M Sinan (The Turkish Journal of Pediatrics, 2018)
We retrospectively evaluated autopsies performed on 151 non-immune hydrops fetalis (NIHF) cases to determine the etiology and pathological findings. Further, cases identified between 1980 and 2004 were compared with those identified between 2005 and 2015 to investigate the improvement of diagnostic performance of our institution. The mean gestational age during the fetal autopsy was 25 weeks. There were 30 live-born infants in the study group. The etiology of NIHF could be determined in 91 cases (60.3%), while it remained undefined in remaining 60 cases. The most commonly associated pathological conditions were cardiovascular malformations (11.3%), followed by chromosomal abnormalities (9.3%). Prior to 20th gestation week, genetic anomalies and cystic hygromas were the most common etiological factors, and after 30 weeks of gestation, cardiac abnormalities were found to be the most common causes. With time, the rate of undefined cases decreased from 48.4% to 33.75%. NIHF is a complex medical condition necessitating a multidisciplinary management approach. Progress in molecular genetics and imaging techniques is expected to improve diagnostic performance for rapid and better identification.
Keywords: congenital malformations; etiology; fetal autopsy; nonimmune hydrops fetalis; perinatal autopsy